Insoluble low-density lipoprotein-proteoglycan complexes enhance cholesteryl ester accumulation in macrophages. - Salisbury, B. G. (1985)
The interaction of arterial proteoglycans (PGs) and low-density lipoproteins (LDLs) has been postulated to be an important factor in extracellular cholesterol accumulation in the arterial wall. In the present study, insoluble complexes of LDL and PG (LDL-PG) were prepared and their effects on cholesteryl ester accumulation in mouse peritoneal macrophages was tested. The cholesteryl ester content of macrophages incubated with LDL-PG for 3 days was greater than 20 times that observed in cells incubated with LDL alone. The uptake of 125I-LDL by macrophages was markedly stimulated if LDL was incorporated into a complex with PG. However, in contrast to either LDL or acetylated LDL (ALDL), the extent of subsequent degradation of LDL-PG by the cells was reduced. The uptake and degradation of LDL-PG complexes stimulated macrophage incorporation of 14C-oleic acid into cholesteryl oleate 4- to 5-fold over LDL alone; however, esterification was significantly less than that observed with ALDL, even though more LDL-PG was degraded. Ultrastructurally, macrophages incubated with LDL-PG complexes contained lipid droplets as well as numerous phagocytic vacuoles often containing material similar in appearance to insoluble complexes. These results demonstrate that components of the extracellular matrix, such as PG, can modify the catabolism of LDL by scavenger cells. This phenomenon may be potentially important with respect to foam-cell genesis from macrophages in the arterial wall.